Development of an Easy-To-Use Microfluidic System to Assess Dynamic Exposure to Mycotoxins in 3D Culture Models: Evaluation of Ochratoxin A and Patulin Cytotoxicity - Veronica Zingales; Caterina Piunti; Sara Micheli; Elisa Cimetta; María-José Ruiz (Foods)
Mycotoxins are among the most concerning natural toxic food contaminants. Over the years, significant efforts have been made to characterize the risk associated with their exposure. However, assessing their toxicity has so far been elusive due to the lack of adequate models that closely mimic the physiological conditions of human cells in vivo. Here, we present the SpheroFlow Device (SFD), an efficient microfluidic platform designed, manufactured, and validated to evaluate mycotoxin-induced cytotoxicity under dynamic and continuous exposure in 3D culture settings. In the present study, we integrated human neuroblastoma SH-SY5Y spheroids into the SFD to assess the acute toxicity induced by the mycotoxins ochratoxin A (OTA) and patulin (PAT). The developed system enabled qualitative and quantitative measurements of concentration–response relationships and provided accurate control over the culture microenvironment. Our findings show that by enhancing 3D culture model by applying dynamic flow, SH-SY5Y spheroids exhibited different sensitivities to OTA and PAT compared to conventional static SH-SY5Y spheroids, confirming the critical role of culture models in mycotoxin toxicity assessment. This is the first study assessing the neurotoxicity of OTA and PAT on 3D neuroblastoma spheroids considering the contribution of fluid flow.